To Study the Prescribing Pattern of Drugs in Dengue Patients of a Tertiary Care Hospital: A Prospective and Observational Study - Biradar, S.M.; Maurya, K.; Naikal, A.; Sarnadgowd, S.; Honnutagi, Rajesh M.; Kattimani, Ravi; B., Shivakumar; Kallyanappagol, V.T. (International Journal of Scientific Research in Biological Sciences, 2020)
Dengue fever (DF) is an acute febrile illness which is transmitted by mosquito bite. Annually 5 lakhs of patients are hospitalized and more than 20,000 deaths are reported worldwide. Till today there is no specific therapy available for DF, therefore it is very essential to study the prescribing pattern of drugs among dengue patients in order to make the pharmacotherapy streamline and reduce the mortality rate. A Prospective observational prescription pattern study was conducted for a period of six months in a tertiary care hospital. The sample size of the study was 100 from medicine and pediatric departments and relevant information were extracted from respective files and selected patients. A total of 661 drugs were prescribed among selected dengue patients, in whom 145 were anti-invectives, out of them 143 drugs were antibiotics, Cefixime contributes 35% and followed by Doxycyclin 25.8% and remaining 516 drugs were as supportive therapy. DF was more prevalent in males and prominent in age group of 11-20 years. As concern with the laboratory diagnosis, it was seen that the NS1positive were 97% and IgM positive were 3%, indicates the most of the patients were brought to the hospital in time, because the NS1 is detected early stage of dengue infection. The hematological values (SBP, DBP, PCV, PLT & TC) were in the optimal range indicating the treatment was started abruptly and prescription was most appropriate to the medical condition of patients.